Adenosine DeaminaseActivity IN p - Thalass emia - AI- Hakeem, T. M.A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The activity Â·of adenosine dcaminase enzyn1eÂ· has  been  investigated in   normal  and   thalassaemic  sera.  The  data  obtaiJ1ed were   refl  cts   an elevation  of' the  enzyme   ctivity in thalassaemic samples compared with those  of  healthy  normal objects. The  study  was  carried  out  with  (6.5)PH value  and  37C   as ma.x.Lmum  temperature. This  study  was comprehensive to the electrophopretic behavior of the hemolysate serum   in a step  of electrophoresis analysis of the thalassaemic-and normal  hemoglobin.